ANALYZING STUDENTS' CULTURAL KNOWLEDGE IN THE TRANSLATION OF SHORT FUNCTIONAL TEXTS - Ghayatri Anandhia Putri, - (2021)
As a process of transferring meaning from a source language to a target language, translation plays an important role in translating the cultural items of a particular language. The main problem of student translators to do this is lacking of cultural knowledge contained in the target language. This study aims to investigate the cultural knowledge drawn upon by the student translators in the translation practices and to reveal techniques used by the students in translating short functional texts. This study involving third-semester students taking translation course, and was conducted by using a qualitative method with a case study design. The data were collected through classroom observation and students' documents. The data of translation texts were analyzed by using Newmark's (1988) cultural categories in classifying culture-specific items and Molina and Albir's (2002) translation techniques. The results of the study showed that the cultural knowledge drawn upon by the students in translation included the cultural competence and culture-specific items. The study also found that the results of the students' translation techniques in translating short functional texts covered adaptation, borrowing, literal translation, and transposition. The results also suggest that cultural knowledge should be taught to students in the early stage of studying translation course.